Attacking inequality in the health sector : a synthesis of evidence and tools - Yazbeck, Abdo (World Bank e-Library., 2009)
The last 10 years have seen a resurgence in interest and research around inequalities in the health sector. While a disproportionate share of the new research has focused on measuring inequality in the health sector, work is emerging on how to understand the causes of inequality and on identifying successful approaches for tackling the problem. This book summarizes the operational lessons emerging from this new focus. It is intended to be an operational resource for change agents within and outside government in low and middle countries committed to improve access and use of critical health se.